Heterologous expression of endo-beta-1,4-D-glucanase from Clostridium cellulovorans in Clostridium acetobutylicum ATCC 824 following transformation of the engB gene. - Kim, A Y (1994)
Heterologous expression of the Clostridium cellulovorans engB gene by Clostridium acetobutylicum BKW-1 was detected as zones of hydrolysis on carboxymethyl cellulose (CMC) Trypticase glucose yeast plates stained with Congo red. The extracellular cellulase preparation from C. acetobutylicum BKW-1 has a specific activity towards CMC which is more than fourfold that present in C. acetobutylicum ATCC 824. Western blot (immunoblot) analysis using the C. cellulovorans anti-EngB primary antibody demonstrated that an additional 44-kDa protein band was present in the supernatant derived from C. acetobutylicum BKW-1 but was not present in ATCC 824 or ATCC 824(pMTL500E).